2005
DOI: 10.1002/erv.644
|View full text |Cite
|
Sign up to set email alerts
|

FPI profiles in a European sample of 1068 female patients suffering from anorexia or bulimia nervosa

Abstract: Thirty‐two centres from nine European countries participated in a research programme about eating disorders. This study presents results of patients aged 17–26 years suffering from anorexia (N = 418) and bulimia nervosa (N = 650) according to DSM‐IV criteria (American Psychiatric Association, 1994). Patients' personality profiles were assessed with the revised version of the Freiburger Personality Inventory (FPI‐R). Compared to the comparison subjects, the eating‐disordered patients showed lower life satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…While several additional personality traits have been linked to EDs and disordered eating behavior in young adult and adult samples, studies examining these links in adolescents are limited and, in some cases, diverge from the young adult and adult literature. For instance, two studies of young adults found that extraversion is lower among those with AN‐R, AN‐B/P, or BN, relative to young adults without EP (without controlling for other psychopathology; Massoubre et al, 2005; Tasca et al, 2009), whereas a study of adolescents did not find an association between extraversion and disordered eating behaviors (Gual et al, 2002). One review (Farstad et al, 2016) noted that discrepancies in the literature pertaining to extraversion and EP may be due to differences between studies that examine subclinical disordered eating symptoms (i.e., Gual et al, 2002) rather than clinical EDs, further highlighting the importance of examining personality across a range of EP severities.…”
Section: Introductionmentioning
confidence: 99%
“…While several additional personality traits have been linked to EDs and disordered eating behavior in young adult and adult samples, studies examining these links in adolescents are limited and, in some cases, diverge from the young adult and adult literature. For instance, two studies of young adults found that extraversion is lower among those with AN‐R, AN‐B/P, or BN, relative to young adults without EP (without controlling for other psychopathology; Massoubre et al, 2005; Tasca et al, 2009), whereas a study of adolescents did not find an association between extraversion and disordered eating behaviors (Gual et al, 2002). One review (Farstad et al, 2016) noted that discrepancies in the literature pertaining to extraversion and EP may be due to differences between studies that examine subclinical disordered eating symptoms (i.e., Gual et al, 2002) rather than clinical EDs, further highlighting the importance of examining personality across a range of EP severities.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, eating problems have been found to be negatively associated with Extraversion (Brookings & Wilson, 1994). Women with AN tend to be less extraverted than controls (Massoubre et al, 2005;Solyom et al, 1982). We therefore expected with women with AN to score lower than never-ill women on the Extraversion subscale of the SMS.…”
Section: Introductionmentioning
confidence: 95%